Transport of Antarctic stratospheric strongly dehydrated air into the troposphere observed during the HALO-ESMVal campaign 2012 - Rolf, C.; Afchine, A.; Bozem, H.; Buchholz, B.; Ebert, V.; Guggenmoser, T.; Hoor, P.; Konopka, P.; Kretschmer, E.; Müller, S.; Schlager, H.; Spelten, N.; et al. (Atmospheric Chemistry and Physics, 2015)
Dehydration in the Antarctic winter stratosphere is a well-known phenomenon that is annually observed by satellites and occasionally observed by balloon-borne measurements. However, in situ measurements of dehydrated air masses in the Antarctic vortex are very rare. Here, we present detailed observations with the in situ and GLORIA remote sensing instrument payload aboard the German aircraft HALO. Strongly dehydrated air masses down to 1.6 ppmv of water vapor were observed as far north as 47° S in an altitude between 12 and 13 km in the lowermost stratosphere. The dehydration can be traced back to individual ice formation events above the Antarctic Peninsula and Plateau, where ice crystals sedimented out and water vapor was irreversibly removed. Within these dehydrated stratospheric air masses, filaments of moister air reaching down to the tropopause are detected with the high-resolution limb sounder, GLORIA. Furthermore, dehydrated air masses are observed with GLORIA in the Antarctic lowermost stratosphere down to 7 km. With the help of a backward trajectory analysis, a midlatitude origin of the moist filaments in the vortex can be identified, while the dry air masses down to 7 km have stratospheric origins. Antarctic stratosphere–troposphere exchange (STE) and transport of dehydrated air masses into the troposphere are investigated. Further, it is shown that the exchange process can be attributed to several successive Rossby wave events in combination with an isentropic exchange of air masses across the thermal tropopause. The transport into the troposphere is caused by air masses that are detached from the potential vorticity (PV) structure by Rossby wave breaking events and subsequently transported diabatically across the dynamical tropopause. Once transported to the troposphere, air masses with stratospheric origin can reach near-surface levels within several days.